2009
DOI: 10.1177/0095798409353754
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Coparenting Relationship Quality in African American Single Mother Families: An Ecological Model

Abstract: Nonmarital coparents, or adults who assist mothers with childrearing, play a significant role in the lives of African American single mothers and their children. Yet relatively little research has examined correlates of the quality of the coparenting relationship in these families. Using a broad ecological framework, the current study examined correlates of maternal-report of coparenting relationship quality in a sample of 242 low-income African American single mother families in the southeastern United States… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…Coparent and mother income, as well as maternal education, were associated with the outcome of interest; therefore, the authors controlled for these demographic variables in the following analyses. The predictor variables were entered beginning with those most distal to the child and progressing to those most proximal to the child (Jones, Foster et al., ; Sterrett, Jones, Forehand, & Garai, ): Block 1: coparent household income, mother‐household income, and mother education level; Block 2: maternal (or coparent) depression; Block 3: mother–coparent conflict (or coparent–mother conflict); and Block 4: maternal–youth (or coparent–youth) relationship quality and maternal (or coparent) monitoring of youth activities.…”
Section: Resultsmentioning
confidence: 99%
“…Coparent and mother income, as well as maternal education, were associated with the outcome of interest; therefore, the authors controlled for these demographic variables in the following analyses. The predictor variables were entered beginning with those most distal to the child and progressing to those most proximal to the child (Jones, Foster et al., ; Sterrett, Jones, Forehand, & Garai, ): Block 1: coparent household income, mother‐household income, and mother education level; Block 2: maternal (or coparent) depression; Block 3: mother–coparent conflict (or coparent–mother conflict); and Block 4: maternal–youth (or coparent–youth) relationship quality and maternal (or coparent) monitoring of youth activities.…”
Section: Resultsmentioning
confidence: 99%
“…With respect to coparenting, instrumental and emotional supports from neighbors may provide dual-earner parents with resources that allow them to better coordinate their work and parenting responsibilities (Voydanoff, 2004). In contrast, neighborhood disadvantage (i.e., poverty, crime, and disorder), has been found to compromise the quality of interparental relationships (Kiser & Black, 2005) and undermine coparenting quality for single-parent African American mothers (Sterrett, Jones, Forehand, & Garai, 2010). Thus, we expected community cohesion to be positively associated with coparenting support and inversely related to coparenting conflict.…”
Section: Coparenting During Adolescencementioning
confidence: 99%
“…Given the role of stressors and supports in other features of family functioning, and the significance of coparenting for individual and family well-being, researchers have recently started to explore socioeconomic factors as predictors of coparenting among African American single mothers (Sterrett, Jones, Forehand, & Garai, 2010) and nonresident fathers (Arditti & Kelly, 1994; Bronte-Tinkew & Horowitz, 2009). In research on coparenting evaluations of nonresident fathers, Arditti and Kelly (1994) found that education was positively related to coparenting evaluations, and, among primarily African American nonresident fathers, higher income and education were related to more perceived coparenting support (Bronte-Tinkew & Horowitz, 2009).…”
Section: The Sociocultural Contexts Of Coparenting: Stressors and Sup...mentioning
confidence: 99%